2017
DOI: 10.1089/gtmb.2016.0197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Suitability of the Most Common Ancient DNA Quantification Methods

Abstract: Methods based on the quantification of the total amount of DNA in samples are unsuitable for ancient samples as they overestimate the amount of DNA presumably due to the presence of microbial DNA. Real-time qPCR methods give undervalued results due to DNA damage and the presence of PCR inhibitors. DNA quantification methods based on fragment analysis show not only the quantity of DNA but also fragment length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This approach has been extensively used for microRNA analysis of plasma samples . The estimation of the isolated samples has been performed by NanoDrop Nucleic Acid Quantification procedure described by Brzobohatá et al (2016) . For each RNA extraction, 800 μL of plasma were added with 2400 μL TRIzol LS.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been extensively used for microRNA analysis of plasma samples . The estimation of the isolated samples has been performed by NanoDrop Nucleic Acid Quantification procedure described by Brzobohatá et al (2016) . For each RNA extraction, 800 μL of plasma were added with 2400 μL TRIzol LS.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have previously compared different NGS library quantification methods and shown contradictory results (Brzobohatá et al, 2017;Hussing et al, 2015;Katsuoka et al, 2014;Laurie et al, 2013;Nakayama et al, 2016;Robin et al, 2016;White et al, 2009). Hussing with colleagues quantified dsDNA oligos and revealed that BioAnalyzer, TapeStation, and Qubit instruments give concentrations closest to the expected (Hussing et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Real-time polymerase chain reactions did not allow for concentration estimation by under-measurement. The most reliable method is fragment analysis, which helps to determine the concentration of DNA and the length of a given fragment [78].…”
Section: Extraction Of Ancient Dnamentioning
confidence: 99%